Elastin Expression is the Strongest Risk Factor for Developing Pelvic Organ Prolapse - Cessaria, Djusiana (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To compare elastin expression in the anterior vaginal wall of women with and with no pelvic prolapse. Methods: The research was conducted in RS Dr. Wahidin Sudirohusodo and other network hospitals of Obstetrics and Gynecology Department of Hasanuddin University, Makassar. Full-thickness specimens were obtained from the anterior vaginal wall of women having a large prolapse repaired (stage III or IV; prolapse group, 34) and the same location in patients with no prolapse having abdominal and vaginal hysterectomy (control group, 35). The expression of elastin was measured by immunohistochemistry on tissue sectioned. The examiner was unaware of sample identity and the patientsâ clinical history. The result then analyzed with p 4000 gr weight (p=0.572); age, parity, menopausal status, and body mass index were significantly different between the groups (0.001; 0.035; 0.011; 0.002; respectively). Immunohistochemical staining indicated that elastin expression in the prolapse group was lower (p=0.009). Elastin expression appeared to be stable with increasing of age, parity, menopausal status, history of bearing baby 4000 gr. weight and Body mass Index in the prolapse group. But multiple logistic regression revealed that elastin have the highest influence to prolapse among the risk factors mentioned (Exp.B =6.252). Conclusion: In this case-control study, the elastin expression were significantly lower in the vaginal wall of patients with a large prolapse. Instead of influence by other risk factors, elastin is the strongest risk factor for developing prolapse among other risk factors. This result is expected to be able to give explanation for the development of prolapse in women without risk factors such is young women and nullipara. [Indones J Obstet Gynecol 2013; 1-4: 204-8] Keywords: elastin, prolapse, women